Citra Tubuh, Kecukupan Gizi, Status Gizi, dan Status Anemia pada Wanita Pranikah - Ardiyanti, Aanisah; Melani, Vitria; Nadiyah, -; Sitoayu, Laras; Wahyuni, Yulia (Universitas Muhammadiyah Semarang, 2021)
Health is the one of readiness factors in marriage. Towards the wedding, usually the body image will be a concern. A diet to get the ideal body is often to found. The results showed that the percentage of anemia in WUS who were not married was greater than WUS who were already married. This study aimed to determine the relationship of body image, level of nutritional adequacy, nutritional status, and anemia status in premarital women.An observational study with cross sectional approach. A number of 65 respondents were selected by accidental sampling. The data were obtained through interviews using questionnaire (respondent characteristics, body shape questionare-34), anthropometric measurements (weight, height, body mass index, nutritional status), and blood sampling (hemoglobin levels). The data were analyzed using Chi-Square Test.The results showed a significant relationship between body image and anemia status (p<0,05). There was no significant relationship between the level of energy sufficiency, protein, fat, iron, zinc, and vitamin C with anemia status (p>0,05). There was no significant relationship between nutritional status and anemia status (p>0,05). The conclusion is that only body image has a significant relationship to anemia status.Key words : anemia, body image, nutrition